Preparation of procyanidin B2 from apple pomace and its inhibitory effect on the expression of cyclooxygenase-2 in lipopolysaccharide-treated RAW264.7 macrophages - Huawei Zhang; Chen Ying (Bangladesh Pharmacological Society, 2011)
Dimeric procyanidin B2 (PB2) is one of phenolic compounds in apple pomace, an agro-industrial byproduct in apple juice processing. This work focused on purification of PB2 from apple pomace using sephadex column chromatography and its potential effect on lipopolysaccharide (LPS)-induced inflammation using RAW264.7 macrophages. PB2 with the purity of 72.28 ± 1.85% was successfully afforded using resin and gel column chromatographic technique. Anti-inflammatory tests suggested that the expression of cyclooxygenase-2 (COX-2) in LPS-induced murine RAW264.7 macrophages was suppressed in a PB2 concentration-dependent manner. PB2 at no less than 50 ?g·mL-1 could significantly suppress inflammation in the LPS-induced cells. Moreover, this suppressive effect was not correlated with PB2 pretreating. However, the COX-2 expression was not reduced in LPS pretreatment way followed by PB2 exposure, which suggested that PB2 has no repairing function. The results showed that high pure PB2 prepared from apple pomace has a remarkable anti-inflammatory property.